Effect of Moringa Oleifera Leaf Extract on FGF21 mRNA Expression in Male Wistar Rats’ Skeletal Muscle Under Sedentary Condition - Titing Nurhayati; Karen Lolinhandary (Althea Medical Journal)
Background : Fibroblast growth factor 21 (FGF21) is a muscle-derived myokine whose expression changes in response to elevated reactive oxygen species (ROS), primarily generated by cytochrome c oxidase complex IV (COX IV) in skeletal muscle. Moringa oleifera (MO) is known for its antioxidant potential, which may influence FGF21 expression and oxidative stress pathways. This study aimed to evaluate the effects of MO leaf extract on FGF21 mRNA expression and mitochondrial oxidative capacity in skeletal muscle under sedentary conditions.